Quantifying the hydrological contribution of glaciers in southwestern Norway at the beginning of the 21st century - Yongmei Gong; Sangita Tomar; Irina Rogozhina; Stefano Basso (Journal of Hydrology: Regional Studies)
Study region: The research is conducted for nineteen glacierized basins in southwestern Norway during the early 21st century. Study focus: The study utilizes a process-based, distributed snow evolution model to carry out high-resolution simulations of glacier surface mass balance and catchment runoff. The model is constrained by observations from fifteen glaciers and evaluated against measured discharge from eight river basins. We investigate the temporal and spatial distribution of surface mass balance and catchment runoff, and analyze the contribution of rainfall, snow and glacier meltwater to the total runoff. Finally, we examine the relationship between interannual variability of discharge and glacier cover. New hydrological insights for the region: The study reveals that glaciers in our study region provide 20.9 % and 19.5 % of the annual and summer runoff on average across different river basins. Snow meltwater is the prevailing runoff component throughout the year across most basins, whereas glacier meltwater is the primary contributor to the summer and autumn runoff for basins with glacier cover > 30 %.The interannual variability of discharge decreases with increasing glacier cover without reaching a local minimum. The sensitivity of discharge variability to temperature exceeds that to precipitation only at high glacier cover (42.1 %).